2021
DOI: 10.1002/cctc.202001757
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Electro‐Biocatalysis for Amine Alkylation with Alcohols

Abstract: The integration of electro and bio‐catalysis offers new ways of making molecules under very mild, environmentally benign conditions. We show that TEMPO mediated electro‐catalytic oxidation of alcohols can be adapted to work in aqueous buffers, with minimal organic co‐solvent, enabling integration with biocatalytic reductive amination using the AdRedAm enzyme. The combined process offers a new approach to amine alkylation with native alcohols, a key bond formation in the chemical economy that is currently achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Cyanobacteria, thanks to their photoautotrophic metabolism, require only sunlight, water, and minimal nutrients to enable the direct conversion of atmospheric CO 2 to a plethora of platform chemicals and biofuels [73,74] . Moreover, by combining the capacity of cyanobacteria for oxygenic CO 2 fixation with metabolic pathway engineering and synthetic biology, sequestered carbon can be redirected into new biochemical pathways that enable the synthesis of a variety of commodity chemicals from CO 2, water, and visible light [7–79] . Several proof‐of‐concept studies, ranging from fine to bulk chemicals, have demonstrated their potential [76] and some reactions (e. g., ethanol production) have been scaled up to pilot plant level [80] …”
Section: Power To Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria, thanks to their photoautotrophic metabolism, require only sunlight, water, and minimal nutrients to enable the direct conversion of atmospheric CO 2 to a plethora of platform chemicals and biofuels [73,74] . Moreover, by combining the capacity of cyanobacteria for oxygenic CO 2 fixation with metabolic pathway engineering and synthetic biology, sequestered carbon can be redirected into new biochemical pathways that enable the synthesis of a variety of commodity chemicals from CO 2, water, and visible light [7–79] . Several proof‐of‐concept studies, ranging from fine to bulk chemicals, have demonstrated their potential [76] and some reactions (e. g., ethanol production) have been scaled up to pilot plant level [80] …”
Section: Power To Chemicalsmentioning
confidence: 99%
“…Similarly, Greany and co‐workers combined (2,2,6,6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO)‐catalyzed electrochemical oxidation of alcohols with enzymatic reductive amination of the resulting ketones to afford a mild and environmentally attractive route to chiral amines from alcohols (see Figure 4) in an aqueous medium [41] …”
Section: Power To Chemicalsmentioning
confidence: 99%
“…Besides TM and organocatalysts, the use of light or electrical energy to promote chemical transformations have recently emerged as new alternatives to these “classical” catalytic methodologies. Examples of such cascades have already been reported [74,75] and will also be the focus of extensive study in the coming years. The use of models to optimise multistep enzymatic cascades [76] can potentially be extended to multicatalytic processes to make them more efficient.…”
Section: Discussionmentioning
confidence: 87%
“…Biocatalysis can be integrated into syntheses that involve chemocatalysis, photocatalysis, 202 and electrocatalysis. 203 For example, the combination of asymmetric organo-and biocatalytic reactions in organic media has been used to synthesize chiral 1,3-diols. 204 A PBR of acyltransferase on a glyoxyl agarose support performed N-and O-acylation of alcohols with vinyl 4- nitrobenzoate in toluene.…”
Section: Could Bementioning
confidence: 99%
“…Biocatalysis can be integrated into syntheses that involve chemocatalysis, photocatalysis, and electrocatalysis . For example, the combination of asymmetric organo- and biocatalytic reactions in organic media has been used to synthesize chiral 1,3-diols …”
Section: Enzymatic and Chemo-enzymatic Cascade Processesmentioning
confidence: 99%